Occlusion and Temporomandibular Function among Subjects with Mandibular Distal Extension Removable Partial Dentures - N. H. J. Creugers; D. J. Witter; A. Van 't Spijker; A. E. Gerritsen; C. M. Kreulen (International Journal of Dentistry)
Objective. To quantify effects on occlusion and temporomandibular function of mandibular distal extension removable partial dentures in shortened dental arches. Methods. Subjects wearing mandibular extension removable partial dentures (n=25) were compared with subjects with shortened dental arches without extension (n=74) and with subjects who had worn a mandibular extension removable partial denture in the past (n=19). Subjects with complete dentitions (n=72) were controls. Data were collected at baseline and at 3-, 6-, and 9-year observations. Results. Occlusal activity in terms of reported awareness of bruxism and occlusal tooth wear of lower anterior teeth did not differ significantly between the groups. In contrast, occlusal tooth wear of premolars in shortened dental arches with or without extension dentures was significantly higher than in the controls. Differences amongst groups with respect to signs and symptoms related to temporomandibular disorders were not found. Occlusal support of the dentures did not influence anterior spatial relationship. Occlusal contacts of the denture teeth decreased from 70% for second premolars via 50% for first molars, to 30% for second molars. Conclusions. Mandibular distal extension removable partial dentures in moderate shortened dental arches had no effects on occlusion and temporomandibular function.